Kult świętych serbskich w monasterach Wielkiego Księstwa Litewskiego do końca XVI wieku - Chomik, Piotr (Elpis, 2014)
The cult of the saints, especially in the sixteenth century, was an important part of religious literature in the Polish- Lithuanian state, due to the Reformation and Counter-Reformation, but also because of the religious Catholic-Orthodox polemics on the eve of the Union of Brest. Among Serbian and South-Slavonic saints the most famous were: St. Paraskeva- Petka of Tyrnovo, St. Sava Serbian, St. Simon and St. John of Suchava. The presence of South-Slavonic element in the liturgical tradition of the Orthodox Church in the Polish-Lithuanian state is the local specificity that distinguishes Orthodoxy in the Republic and the Grand Duchy of Lithuania from the Orthodox Church in the great Russian state.